Next-Generation Sequencing Reveals a Very Low Prevalence of Deleterious Mutations of Homologous Recombination Repair Genes and Homologous Recombination Deficiency in Ovarian Clear Cell Carcinoma - Liu, Hangqi; Zhang, Zhiwen; Chen, Longyun; Pang, Junyi; Wu, Huanwen; Liang, Zhiyong (Frontiers in Oncology, 2022)
Ovarian clear cell carcinoma (OCCC) is aggressive and drug-resistant. The prevalence of homologous recombination repair (HRR) gene mutations and homologous recombination deficiency (HRD) remains largely unknown. It is also not clear whether the commonly used molecular-based classification for endometrial carcinoma (EC) is potentially applicable in OCCC. In this study, surgically resected samples were collected from 44 patients with OCCC. Genomic alterations were determined using next-generation sequencing. HRD was estimated by genomic instability. Of 44 patients with OCCC, two (4.5%) harbored likely pathogenic mutations in HRR genes. Notably, no pathogenic or likely pathogenic mutations were found in BRCA1/2. A total of 24 variants of uncertain significance (VUS) in HRR-related genes occurred in 18 (40.9%) of patients. HRD was observed in only one case (2.3%). In addition, TP53 mutation and microsatellite instability-high (MSI-H) were identified in three (6.8%) and one patient (2.3%), respectively. TP53 mutation was significantly associated with disease-free survival and overall survival. No POLE mutations were found. In conclusion, our results revealed a very low prevalence of HRR gene mutations and HRD in OCCC. Moreover, TP53 mutations and MSI-H are uncommon, while POLE mutations are extremely rare in OCCC. Our findings indicate that the evaluation of HRR gene mutations, HRD status, POLE mutations and MSI-H may have limited clinical significance for OCCC treatment and prognostic stratification.